Über eine Gruppe hochmittelalterlicher Prunksporen im Südwesten der Ostsee - Biermann, Felix (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
A small group of richly decorated spurs has been known for a long time for their characteristic non-ferrous metal covering as well as massive bronze or brass thorn points. Most of them have been found in in the states of Hamburg and Schleswig-Holstein. They are so similar that they could have been manufactured, if not in the same workshop, at least in the same region. The embossed metal sheath, reminiscent of the Late Slavic technology of sheath fittings, could indicate a the Slavic craft tradition. The latest find from a deserted village of Kastaven near Sähle, Oberhavel district in northern Brandenburg, sheds new light on this group of objects. The Kastaven spur has been found in the central area of the settlement which existed between the early 13th and the 15th centuries, in the vicinity of ruins of a church or a churchyard. The spur was probably lost at the village foundation phase, in the early 13th century. This context is of importance to the disputed chronology of the entire spur group, dated back to the late 12th and the early 13th centuries. The finds in Hamburg, Holstein, Eastern Mecklenburg and Northern Brandenburg indicate contacts between the élites in the southwest of the Baltic, related to migrations of petty nobility within the German Eastern Settlement or a communication network of the Slavic Leaders in the Abodrite/Mecklenburg cultural area.